2016
DOI: 10.15405/epsbs.2016.11.02.30
|View full text |Cite
|
Sign up to set email alerts
|

Shopper Centric Category Management in Convenience Stores: a Qualitative Study

Abstract: The literature shows that category management is an important concept and tool for retailers and suppliers, but that there is a trend to move to a more shopper-centric category management approach, linked to the shoppermarketing approach. However, the knowledge on this issue is scarce on some retailing sectors, like convenience stores. The present study is focused on convenience stores, with the main purpose of finding out to what extent non-major food retailers successfully adopt a shopper-centric category ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Twenty articles were identified that described TPP used by manufacturers to influence retailer marketing strategies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Of these, 13 articles were published in the peer-reviewed literature or through conference proceedings and seven articles were published in trade publications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty articles were identified that described TPP used by manufacturers to influence retailer marketing strategies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Of these, 13 articles were published in the peer-reviewed literature or through conference proceedings and seven articles were published in trade publications.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles focused on category management [ 27 , 28 , 31 , 34 , 35 , 37 , 38 , 39 , 41 , 43 , 44 ]. Category management is the collaboration between manufacturers and retailers to make decisions regarding product assortment, space allocation, pricing, and in-store promotion for entire product categories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation